2011
DOI: 10.1007/s11426-011-4396-6
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical properties of heteroaromatic ring-fused (di)benzosiloles

Abstract: Benzosiloles fused to heterocycles such as thiophene, benzothiophene, and benzofuran, and indole-and benzosilole-fused dibenzosiloles were prepared by palladium-catalyzed intramolecular coupling of the corresponding 2-(arylsilyl)aryl triflates in good to high yields. Molecular and crystal structures of 5,7-dihydro-5,5,7,7-tetrakis(1-methylethyl)bis[1]benzosilolo-[2,3-b:3', 2'-d]thiophene, 6-methyl-12,12-diisopropyl-12H-indololo[3,2-b][1]silafluorene, and 5,5,11,11-tetraisopropyl-5,11H-benzosilolo[3,2-c]silaflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 52 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…The photophysical properties of 15c – 15f are summarized in Table , along with those of 3‐methoxy‐ and 3‐dimethylamino‐substituted dibenzosiloles 15a and 15b [18a]. As seen in Figure , the absorption maxima redshifted significantly when D was switched from methoxy to dimethylamino (compare 15a and 15b ) and from dimethylamino to diphenylamino (compare 15c and 15d ), and the electron‐withdrawing nature of A increased (compare 15d , 15e , and 15f ).…”
Section: Organic Chromophores Based On Dibenzosilolesmentioning
confidence: 99%
See 2 more Smart Citations
“…The photophysical properties of 15c – 15f are summarized in Table , along with those of 3‐methoxy‐ and 3‐dimethylamino‐substituted dibenzosiloles 15a and 15b [18a]. As seen in Figure , the absorption maxima redshifted significantly when D was switched from methoxy to dimethylamino (compare 15a and 15b ) and from dimethylamino to diphenylamino (compare 15c and 15d ), and the electron‐withdrawing nature of A increased (compare 15d , 15e , and 15f ).…”
Section: Organic Chromophores Based On Dibenzosilolesmentioning
confidence: 99%
“…In contrast, 3‐D‐7‐A‐substituted dibenzosiloles, which could be regarded as the silicon analogues of the D‐π‐A‐type fluorenes, remained unexplored, probably due to the lack of facile synthetic methods for such unsymmetrical dibenzosiloles. However, the development of the palladium‐catalyzed cyclization of 2‐[3‐(diorganoamino)phenylsilyl]‐4‐cyanophenyl triflates, which gave 15c and 15d in excellent yields as single regioisomers, enabled access to the D‐π‐A‐type dibenzosiloles 15c – 15f , and allowed us to explore the potential of 15 as functional materials (Figure ) [18a]. The formyl and dicyanoethenyl derivatives 15e and 15f were easily obtained by diisobutylaluminum hydride reduction of 15d and Knoevenagel condensation of 15e with CH 2 (CN) 2 .…”
Section: Organic Chromophores Based On Dibenzosilolesmentioning
confidence: 99%
See 1 more Smart Citation
“…41 During our study of the intramolecular coupling reaction, we found that 9q and 9r, originally prepared to demonstrate the reaction scope, exhibited intense violet fluorescence in the solid state, with high quantum yields of 0.51 and 0.70, respectively ( Figure 9). 42,43 The crystal packing of 9q and 9r showed that the molecules in each crystal were well separated from one another, presumably due to the steric bulkiness of isopropyl groups. No p-p stacking, which leads to severe fluorescence quenching, was observed between adjacent molecules.…”
Section: Violet-emissive 9-silafluorenesmentioning
confidence: 99%
“…In other words, aggregationinduced emission was observed for the dibenzosiloles. Notably, 5,5,11,11-tetraisopropyl-5,11H-benzosilolo[3,2-c]silafluorene in microcrystals exhibited violet fluorescence ( max = 396 nm) with a quantum yield of 0.70" [25]. Jingzhi Sun, Ben Zhong Tang, and coworkers reported post-functionalization of disubstituted polyacetylenes via click chemistry [26].…”
Section: Organic Biological and Polymeric Chemistrymentioning
confidence: 99%